2008
DOI: 10.1007/s10620-008-0498-1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of iNOS Inhibitors and Hyperbaric Oxygen Treatment in a Rat Model of Experimental Colitis

Abstract: Both HBO and AMG were significantly effective in preventing weight loss, reducing NO activities, and severity of colitis, when comparing HBO and AMG separately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 40 publications
1
7
0
2
Order By: Relevance
“…The results suggest the development of liver necrosis and cholestasis, which is evident after 72 h; however, lipid peroxidation started after 1-2 weeks of BDL [32]. Our results are in agreement with Ercin et al [33], who reported that in BDL rats, the activity of the antioxidant systems diminished, which is responsible for the inhibition of the free oxygen radicals. The administration of albumin significantly increased the catalase activity and GSH level as well as reduced the MDA level and thus reduced reactive free radical induced oxidative damage, protected the tissues from highly reactive hydroxyl radicals and attenuated lipid peroxidation in the kidney of the BDL rats.…”
Section: Discussionsupporting
confidence: 92%
“…The results suggest the development of liver necrosis and cholestasis, which is evident after 72 h; however, lipid peroxidation started after 1-2 weeks of BDL [32]. Our results are in agreement with Ercin et al [33], who reported that in BDL rats, the activity of the antioxidant systems diminished, which is responsible for the inhibition of the free oxygen radicals. The administration of albumin significantly increased the catalase activity and GSH level as well as reduced the MDA level and thus reduced reactive free radical induced oxidative damage, protected the tissues from highly reactive hydroxyl radicals and attenuated lipid peroxidation in the kidney of the BDL rats.…”
Section: Discussionsupporting
confidence: 92%
“…Two studies reported HBOT significantly increased glutathione peroxidase and superoxide dismutase levels [60,61]. HBOT also decreased nitric oxide [58,61,63] and nitric oxide synthase levels [63,64,66]. Finally, in one study, HBOT decreased prostaglandin E 2 levels [64].…”
Section: Resultsmentioning
confidence: 99%
“…Sustained, high levels of NO production, especially when mediated by iNOS in the colon, play a role in the pathology of IBD [2628]. Several synthetic iNOS inhibitors were effective in suppressing DSS-induced colitis symptoms in mice [2628]. Marked elevated levels of PGE 2 and COX-2 were also observed during inflammation, including DSS-induced colonic injury [29].…”
Section: Discussionmentioning
confidence: 99%